Evaluation of the German Version of the Adult Attention-Deficit/Hyperactivity Disorder Self-Report Screening Scale for DSM-5 as a Screening Tool for Adult Attention-Deficit/Hyperactivity Disorder in Primary Care - Ballmann, Cora; Kölle, Markus Alexander; Bekavac-Günther, Ines; Wolf, Florian; Pargent, Florian; Barzel, Anne; Philipsen, Alexandra; Gensichen, Jochen (Frontiers in Psychology, 2022)
Adult Attention deficit/ Hyperactivity Disorder (ADHD) is common, but often undiagnosed. A valid and time-efficient screening tool for primary care is needed. Objective of this study is to evaluate the German version of the Adult ADHD Self-Report Scale for DSM-5 (ASRS-5) and its feasibility, acceptability, and reliability as a screening tool for adult ADHD in primary care. A multi-centered prospective, diagnostic study was performed. We recruited 262 patients in primary care practices and at an ADHD Outpatient Service of a department of psychiatry in Germany. Patients from 18-65 years with suspected or diagnosed ADHD were included by medical doctors, as well as non ADHD patients as “negative controls”. Participants filled in the ASRS-5 and a sociodemographic questionnaire. The Integrated Diagnosis of Adult ADHD, revised version (IDA-R) performed by trained interviewers was used for validation. Feasibility, acceptability and credibility in primary care practices were examined through a semi-structured interview. The German version of the ASRS-5 showed comparable psychometric properties to the English original version (Sensitivity 95.6%, Specificity 72.3%). For factor structure, a parallel analysis suggested one latent dimension. Performing confirmatory factor analysis the best fit was achieved for a general factor with one correlated error. Internal consistency results in Raykovs Omega=0.86 and Cronbachs α=0.88. The ASRS-5 was assessed positively in terms of feasibility, acceptability, and credibility by interviewed general practitioners. Potential problems were raised for “treatment options”, “stigmatization” and “knowledge gaps”. In conclusion the German version of the ASRS-5 offers a promising tool to improve adult ADHD patients’ diagnosis and health care.